First Nations Elders in Northwestern Ontario’s perspectives of health, body image and eating disorders - Alani-Verjee, Taslim; Braunberger, Peter; Bobinski, Tina; Mushquash, Christopher (Te Rau Ora, 2017)
Health, healthy eating, and ideal body image often have been conceptualised from a Eurocentric perspective. Indigenous perspectives may differ, and are necessary to better conceptualise eating disorders among Indigenous peoples. Five First Nations Elders from Northwestern Ontario were interviewed to gain a better understanding of these concepts, and how they may relate to the well-being of youth. Results demonstrate the importance of conceptualising health holistically; the impacts of colonisation on health, well-being, and understandings of self; how the relationships among food, health, and nutrition are complex; and that ideal bodies often have been equated with health and balance. Moreover, participants described how these findings may influence youth and their well-being. This paper demonstrates that, in order to better support the health, well-being, and body satisfaction of First Nations youth, it is essential to understand how these are defined, and how different factors may be of influence.